The built then sell (bts) system in housing industry : obstacles to its implementation in Selangor - Yakob, Hamizah (2010)
The Built then Sell (BTS) system has been an issue in the housing industry since its introduction in 2007. The system was offered as an option to developers due to several problems regarding its implementation. Several developers have opted to use this system in their housing project. Hence, the study focused on the approach used by these developers in implementing BTS system and problems encountered during its implementation. The aim of the study is to identify the obstacles that prevent the implementation of BTS system in Selangor. Three objectives were identified for the study which was, 1) to identify the influence of mechanisms in the implementation of BTS system, 2) to identify the influence of incentives in the implementation of BTS system and 3) to identify the influence of financing in implementing the implementation of BTS system. A case study approach was used in the study. Three case studies were selected in the study due lack of involvement of developer in BTS project. The transcript texts of the taped interview from the case study were compared and interpreted in terms of mechanism, incentives and financing. It was indicated that unclear policy and procedures, lack of rules and regulations, lack of coordination between administrative levels and lack of awareness among home buyers are problems of the existing mechanisms in the BTS implementation. It was further indicate that unattractive and insufficient of provided incentives as well as unskilled, lacking of staff and bureaucratic red tape are problems regarding the incentives. It was identified that lack of financial facilities, misunderstanding of the system and stricter terms and conditions are problems in obtaining bridging finance for BTS projects. Hence, internal funding used to replace end financing under the system. The findings may carry a few implications for the improvement of housing delivery system and parties involved in the housing industry in Malaysia.